Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 8 - Section 8.3 - Polynomial and Rational Functions - Exercise Set: 47



Work Step by Step

If $P(x) = 3x+3$ and $Q(x) = 4x^2-6x+3$ $P(x) + Q(x) = 3x+3 + 4x^2-6x+3 = 4x^2-6x+3x+3+3 = 4x^2-3x+6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.